KEBIJAKAN PIDANA DALAM TINDAK PIDANA KORUPSI OLEH KORPORASI - Wasahua, Idris (Lex Jurnalica, 2024)
AbstractThis research aims to examine three aspects of criminal policy in cases of corruption committed by corporations, as regulated in Law No. 31 of 1999, as amended by Law No. 20 of 2001 on the Eradication of Corruption Crimes. These aspects are: First, criminal policy regarding acts of corruption that can be held accountable to corporations. Second, criminal policy concerning the system of corporate criminal liability in corruption cases. Third, criminal policy related to criminal sanctions that may be imposed on corruption offenses committed by corporations. This research uses normative juridical research methods. This research produces the following conclusions: First, acts of corruption that can be committed and made accountable to corporations include all corruption offenses regulated in Chapter II of the Anti-Corruption Law, where the legal subject of the offense includes the element of